Hubungan Diare Akut dengan Kejadian Kejang Demam Kompleks pada Anak Balita di RSUD Syekh Yusuf Kab. Gowa Tahun 2023-2025 - Andi Diah Putri Kemal; Rauly Rahmadhani; Abd. Rahman; Rizka Anastasia; Rahmi Damis (HB PRESS, 2026)
Complex febrile seizures are a neurological disorder in children aged 6 months to 5 years that may lead to long-term neurological complications. Acute diarrhea, one of the most prevalent infectious diseases in toddlers, can trigger fever, dehydration, and electrolyte disorders that lower the seizure threshold. This study aimed to determine the relationship between acute diarrhea and the incidence of complex febrile seizures in children under five. This was an observational analytical study with a cross-sectional design using secondary data from medical records at Syekh Yusuf General Hospital, Gowa Regency, covering the period 2023–2025. Samples were selected using total sampling, yielding 95 respondents who met the inclusion and exclusion criteria. Data were analyzed using univariate and bivariate analysis with the Chi-Square test via SPSS. Of the 95 respondents, 74 children (77.9%) experienced complex febrile seizures. Among 63 children with acute diarrhea, 59 (93.7%) had complex febrile seizures, compared to only 15 of 32 (46.9%) without acute diarrhea. Chi-Square analysis showed p<0.001 (p-value=0.000), indicating a statistically significant association. Most children with complex febrile seizures had a history of acute diarrhea (79.7%), with a median age of 2 years, and were predominantly male (61.1%). Acute diarrhea was significantly associated with complex febrile seizures in toddlers, as it can cause fever, dehydration, and electrolyte disruption that lower the seizure threshold. Early prevention and management of acute diarrhea and parental education are essential to reduce the risk of complex febrile seizures.